Organoplatinum(II) Cruciform: A Versatile Building Block to Fabricate 2D Microcrystals with Full‐Color and White Phosphorescence and Anisotropic Photon Transport. (27th January 2022) - Xu, Fa‐Feng; Zeng, Wei; Sun, Meng‐Jia; Gong, Zhong‐Liang; Li, Zhong‐Qiu; Zhao, Yong Sheng; Yao, Jiannian; Zhong, Yu‐Wu
Abstract: Conventional square‐planar platinum complexes typically form one‐dimensional assemblies as a result of unidirectional metallophilic and/or π⋅⋅⋅π intermolecular interactions. Organoplatinum(II) complexes with a cruciform shape are presented herein to construct two‐dimensional (2D) microcrystals with full‐color and white phosphorescence. These 2D crystals show unique monocomponent π⋅⋅⋅π stacking, from either the cyclometalating or noncyclometalating ligand, and the bicomponent alternate π⋅⋅⋅π stacking from both ligands along different facet directions. Anisotropic tri‐directional waveguiding is further implemented on a single hexagonal microcrystal. These results demonstrate the great capability of the organoplatinum(II) cruciform as a general platform to fabricate 2D phosphorescent micro‐/nanocrystals for advanced photonic applications. Abstract : The controllable preparations of two‐dimensional phosphorescent crystals remain a challenging task. In stark contrast to the conventional one‐dimensional assemblies of square‐planar platinum complexes, organoplatinum(II) complexes with a cruciform shape form two‐dimensional microcrystals with full‐color and white phosphorescence by unique molecular stackings, opening a new avenue for the preparations of phosphorescent micro/nanostructures for advanced photonic applications.